2021
DOI: 10.24018/ejbmr.2021.6.4.923
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact on Online Purchasing Behaviour in Oman and the Future of Online Groceries

Abstract: This paper studies the impact of COVID-19 on customers purchasing behaviour and predicts the future of logistics movements in online groceries in Oman. The paper aims to study the impact of COVID-19 on electronic groceries and E-Shoppers purchasing behaviour and investigate the future of online groceries. The research used an online qualitative survey that targeted the grocery consumers in Oman, including citizens and residents, to evaluate their purchasing behaviour and satisfaction with online grocery shoppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Numerous studies have already confirmed the increase in use of OGS during the COVID-19 pandemic worldwide [12][13][14][15][16][17][18][19][20][21][22]. Additionally, Brüggemann and Pauwels [23] found significant differences between also-online and offline-only grocery shoppers in both consumers' attitudes and purchase behavior.…”
Section: Introductionmentioning
confidence: 95%
“…Numerous studies have already confirmed the increase in use of OGS during the COVID-19 pandemic worldwide [12][13][14][15][16][17][18][19][20][21][22]. Additionally, Brüggemann and Pauwels [23] found significant differences between also-online and offline-only grocery shoppers in both consumers' attitudes and purchase behavior.…”
Section: Introductionmentioning
confidence: 95%
“…Several empirical studies reveal the strong contribution of this lifestyle in realizing purchasing goods and services and find the strength of lifestyle in influencing consumption decisions. (AL-Hawari et al, 2021;Matharu et al, 2020;Simanjuntak, 2021;Tan et al, 2021).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Zahra and Anoraga (2021) found a positive relationship between lifestyle on student consumptive behavior. Some other empirical studies have also revealed the strong contribution of this lifestyle in realizing purchasing goods and services (AL-Hawari et al, 2021;Matharu et al, 2020;Simanjuntak, 2021;Tan et al, 2021). This condition tends to be overburdened in terms of their financial ability, which dominantly still relies on pocket money from their parents.…”
mentioning
confidence: 99%
“…They also became more reliant on shelf-stable packaged foods [ 8 ]. The COVID-19 pandemic further altered consumer dietary patterns and food-sourcing strategies, and consumers may now prefer to procure their food through online channels that offer convenient door-to-door delivery services, which are perceived as safer [ 9 ] and more comfortable [ 10 ]; therefore, online food deliveries have become more desirable. Moreover, consumers may now choose the channels that allow them to maintain higher household inventories of staple goods to minimize their need for frequent visits to physical markets.…”
Section: Introductionmentioning
confidence: 99%